The Economic Value of Blockchain Applications: Early Evidence from Asset-Backed Securities - Chen, Xia; Cheng, Qiang; Luo, Ting (Management Science, 2024)
In this paper, we evaluate the economic value of a blockchain application. In the context of asset-backed securities (ABS) issuance in China, where some ABS are issued with blockchain technology and others are not, we find that the use of blockchain significantly reduces the coupon yield at issuance. Compared with other ABS, those issued using blockchain technology experience a decrease of 31.4 basis points in the yield spread, which corresponds to a relative decrease of 13%. We further document that the effect of blockchain is more pronounced for ABS deals rated by less reputable credit rating agencies and agencies that rely more on issuers for their rating business, for revolving ABS, and for ABS with a larger number of underlying assets. We also find that the use of blockchain can reduce the level of retained interest and number of credit enhancement mechanisms. This paper contributes to the literature by providing a small-sample analysis of the economic value of a blockchain application in financial markets. This paper was accepted by Brian Bushee, accounting. Funding: X. Chen and Q. Cheng acknowledge funding provided by the Lee Kong Chian Professorship at Singapore Management University. This work was supported by Singapore Ministry of Education [Grant MOE-T2EP40120-0005]. Supplemental Material: Data are available at https://doi.org/10.1287/mnsc.2023.4671 .